Application of Ancestry Informative Markers to Association Studies in European Americans - Seldin, Michael F.; Price, Alkes L. (PLoS genetics, 2008)
[...]depending on the number of case and control samples and the cost of prescreening with AIM panels, it may be advantageous to first match cases and controls for ancestry. [...]if a variant is more polymorphic or has higher relative risk in samples of a particular ancestry, then a more genetically homogeneous group of subjects (for example, focusing on Ashkenazi Jewish ancestry [14]) may be more likely to reveal that variant.